Pengaruh Penyuluhan Tentang Perubahan Psikologis Pubertas Terhadap Pengetahuan Remaja Terhadap Pubertas Di Desa Kontunaga - Mansyarif, Rosminah; Husuni, Wa Ode Sitti Fidia; Usman, Andi Sri Hastuti Handayani (Program Studi DIV Kebidanan Fakultas Ilmu Kesehatan Universitas Muhammadiyah Gorontalo, 2023)
During adolescence there are many changes both physically and psychologically, as a transition period from children to adults. This causes teenagers to vulnerable experience problems in terms of reproductive health. The aim of this research is to see the effect of providing counseling on adolescents' level of knowledge about psychological changes during puberty. The type of research is experimental with Pre Experimental Design design. The population was all 29 young women in Kontunaga village. Technique uses total sampling, namely the entire population is the sample. The research results found that there was a change in the number of teenagers who had high knowledge before and after the counseling. The results showed that there was an increase number of teenagers who had high knowledge after the counseling, namely pre-test data of 13 people and at the post-test data of 21 people. The results of the Wilcoxon statistical test analysis using SPSS 16, where the significance value is 0.000 < 0.05, which means Ho is rejected and Ha is accepted. It can be concluded that there is an influence of counseling on the level of knowledge of psychological changes during puberty in Kontunaga village teenagers.